Video matting - Rishi Venkat. (2012)
Matting refers to the problem of accurate foreground estimation in images and videos. It is one of the key techniques in many image editing and film production applications, thus has been extensively studied in the literature. With the recent advancements in digital cameras, the use of matting techniques for editing or to create interesting and novel composites has gained increasing interest. Consequently, various matting techniques and systems have been proposed to try to efficiently extract high quality mattes from both still images and video sequences.